DESIGN AND MAKING THE PULLEY AND HOUSING GLOCK FITNESS EQUIPMENT LAT PULL DOWN TO BE SAFE FOR USERS - Diantoro, 08.04.51.0021 Andi (Students Journal of Engineering, 2013)
Pulley is a wheel that rotates on its axis. Pulley used with a chain or rope to lift heavy objects. Pulley can change the direction of the force used to pull or lift objects. Security is very important in penggunanaanya pulley for lifting loads such as fitness equipment. Pulley on fitness equipment designed to avoid the release of the string and the beat of the breakdown of the string. Pulley house is designed to protect the string that can not be separated from the pulley. Housing glock is designed to withstand the buffeting that occurs when a string broke due to the weight Â Keywords: Safety Pulley, Pulley House, Housing Glock